Does science have the answer to most issues of food security? - Marta Musolino; Gabriella Nucera (Journal of Health and Social Sciences)
Today, the attention to food security has grown with the awareness of resources’ scarcity, earth excessive exploitation, population growth and climate change, all factors that are associated with an impelling food emergency. A plethora of theoretical perspectives adopted in analysing food security issue reflects in diverse normative approaches. Some focus on the rapport between population demand and food supply, seeking to reduce the former or increase the latter in order to achieve food security. Applying the technological progress of scientific research will have its positive outcomes: production will increase, keeping prices low; the limited resources will be used more efficiently, decreasing the consumption of water, energy and land; the environment will benefit from a more sustainable production. However, scientific solutions, such as population control, that do not restore individuals’ entitlement to food will be ineffective in preventing food insecurity. Therefore, food security it is not achievable by the sole means of science. A greater quantity of food does not guarantee a more equal distribution of resources. Increasing food production without altering its uneven distribution will only augment this inequality, making who has access to food more secure but not helping who is currently affected by the food insecurity issues. Science can play its role, but development towards the solutions to food insecurity must be led by politics.